2021
DOI: 10.3390/ijerph18126633
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster Randomized Controlled Trial Feasibility Study of a WhatsApp-Delivered Intervention to Promote Healthy Eating Habits in Male Firefighters

Abstract: This cluster randomized controlled trial (CRCT)-designed study aimed to explore the feasibility of a promotion pamphlet and/or WhatsApp as a suitable mode of delivery to promote healthy eating habits with fruit and vegetables (F&V) among firefighters. Convenience and snowball sampling methods were used. Forty-five firefighters from 23 fire stations were recruited and they all received the printed pamphlet, while the intervention group participants (n = 20) received additional teaching material through What… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…This study used social media to overcome the constraints of time and place, and developed an intervention program to reach more truck drivers. Past studies have indicated the use of social media can facilitate access to groups that are not easily accessible, such as patients with AIDS and firefighters [52,53], which was verified by this study.…”
Section: Discussionsupporting
confidence: 81%
“…This study used social media to overcome the constraints of time and place, and developed an intervention program to reach more truck drivers. Past studies have indicated the use of social media can facilitate access to groups that are not easily accessible, such as patients with AIDS and firefighters [52,53], which was verified by this study.…”
Section: Discussionsupporting
confidence: 81%
“…Instead of using a traditional short message service, text messages can now be delivered in the form of voice, images, and videos via general smartphone communication apps such as Telegram and WhatsApp. The advanced features of text messaging may enhance adherence behaviors, resulting in an improvement in BP control [ 51 , 52 ]. Hence, future studies should examine the effect of informative images and videos on HTN management, including BP regulation, medication adherence, and adherence to lifestyle modifications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to dietary training and education sessions, promotional pamphlets and messaging through social media apps have been used to encourage healthy eating habits of fruits and vegetables. Ng et al [ 44 ] conducted an eight-week cluster randomized controlled trial in which they investigated the effects of using WhatsApp, a communication app, to promote healthy eating. The control group received a health promotion pamphlet, and the intervention group received the pamphlet as well as additional educational material through WhatsApp.…”
Section: Resultsmentioning
confidence: 99%
“…The control group received a health promotion pamphlet, and the intervention group received the pamphlet as well as additional educational material through WhatsApp. The content of the material that Ng et al [ 44 ] developed focused on the first four stages of the transtheoretical model (TTM) of behavioral change readiness (precontemplation, contemplation, preparation, and action) to explain the reasoning behind healthy eating habits, state the benefits of incorporating more fruits and vegetables into daily diets, provide various cooking methods for vegetables, and include practical advice for eating enough fruits and vegetables when dining out and eating during special occasions. These materials were sent to the intervention group in intervals of one to two weeks.…”
Section: Resultsmentioning
confidence: 99%